Enhancement problem solving ability in mathematics using active learning strategy type learning starts with a question - M Handayani; E Herlina; K Rahmi; K Yulianti (Pascasarjana Universitas Pendidikan Indonesia, 2019)
This study aims to find out the difference enhancement of mathematics problem-solving ability between students with Active Learning Strategy Type Learning Starts with a Question (LSQ) and students with direct learning. This research was a quasi-experiment by randomized pretest-posttest control group design. The sample was 48 junior high school students in West Sumatra in the even semester of 2017. Observation, documentation, and test used in the data collection method in this study. N-Gain and T-test were are used to analyze the data. N-Gain in LSQ strategy is at a high level, whether N-Gain indirect learning is at a medium level. The Result of this study is that the mathematical problem-solving ability of students using LSQ strategy is better than the mathematical problem-solving ability of students using direct learning.